Design of smart autonomous solar panel with cascaded SEPIC-boost converter for high voltage renewable applications. Issue 1 (31st December 2023) - Kumari, Rubi; Pyakurel, Pawan; Bhattacharya, Dibyadeep; Rai, Bijay; Pandit, Moumi; Sherpa, K.S
ABSTRACT: The most admired alternative to conventional energy sources is solar energy. In north-eastern regions of India, where availability of sun is unpredictable but irradiance level is high, special observation is needed to upgrade the solar collection systems. The main objective of the research work is to develop a renewable system, which can extract maximum voltage using dual axis movable surface and design a cascaded converter, which can further increase the voltage while maintaining high efficiency. The output of the smart independent self-regulating solar panel hardware model proposed in this paper is fed into a DC–DC cascaded Boost-SEPIC system for renewable-based applications. The newly created renewable system is built to move the panel so that the most voltage is extracted. The DC–DC cascaded converter receives power from the solar panel's output. To assess the system's effectiveness and voltage gain, a thorough circuit analysis is carried out. The converter is tested using various duty cycles. With a 50% duty ratio and 90% efficiency, the suggested converter produces a 40 V DC output from a 20 V DC input voltage from a solar panel. Results from an experimental prototype are used to verify the converter's viability.